A common tumour-specific antigen: III. Preparation of small fragments incorporating the cell-sensitizing determinant. - Dickinson, J. P. (Nature Publishing Group, 1980)
Intact cells of various human tumours and tumour cell lines, and acid extracts of various human tumours and normal tissues, each of which react with the lymphocytes of cancer patients as detected by the macrophage electrophoretic mobility (MEM) test, have been subjected to proteolysis. Activity was destroyed by some enzymes, and the apparent molecular size of the active material was reduced by others. An active low-mol.-wt fragment has been partially purified from papain digests of several tumours. Peptides with normal tissue and tumour-characteristic activities have been separated chromatographically from tryptic digests of tumour extracts.